ANALISIS TAX EFFORT DAERAH DI INDONESIA - Ade Aida; Dini Hariyanti; Sumiyarti (Media Ekonomi, 2022)
This study was conducted to analyze the effect of central government transfers on regional taxation efforts covering districts/cities in Indonesia in the 2015-2019 range after the enactment of Law Number 28 of 2009 concerning Regional Taxes and Regional Levie/ Pajak Daerah dan Retribusi Daerah (UU PDRD). This study uses a quantitative analysis approach, with an econometric model of panel data regression (unbalanced panel. The data used is in a span of 5 years, starting from 2015 to 2019 in regencies/cities in Indonesia except for cities in DKI Jakarta Province. The dependent variable used is Tax Effort is used, while the variables used in this study include General Allocation Fund/ Dana Alokasi Umum (DAU), Special Allocation Fund/ Dana Alokasi Khusus (DAK), Revenue Sharing Fund/ Dana Bagi Hasil (DBH), Population, Poor Population, and Administrative Status. Based on the results of panel data processing using regression analysis techniques, it shows that the central government transfer funds allocated to the regions through the General Allocation Fund (DAU) and the Special Allocation Fund (DAK) have a negative effect on tax effort, while the Revenue Sharing Fund (DBH) has a negative effect on tax effort. positive on regional tax effort. In addition, the results of the study also showed that the population had a negative effect on the tax effort, the number of poor people had a positive effect on the tax effort and administrative status which indicated whether the area was included in the status of a city or district area did not affect the regional tax effort. With the research results obtained, it can provide an overview of the behavior of local governments in responding to the mechanism of fiscal decentralization, especially with the many types and amounts of transfer funds to the regions, coupled with the transfer of authority to manage Rural and Urban Land and Building Taxes/ Pajak Bumi dan Bangunan Perdesaan dan Perkotaan (PBB P2) and Land Rights Acquisition Fees and Buildings/ Bea Perolehan Hak Atas Tanah dan Bangunan (BPHTB) become part of the district/city local government.